2017
DOI: 10.1108/raf-01-2015-0006
|View full text |Cite
|
Sign up to set email alerts
|

Do non-staggered board elections matter to earnings quality and the value relevance of earnings and book value?

Abstract: Purpose The purpose of this paper is to examine the impact of non-staggered voting for members of the board of directors on earnings quality and the value relevance of earnings and book value. Design/methodology/approach The authors used a sample of Taiwanese firms whose board was elected as a whole every three years from 2003 to 2013. The authors used multiple regression analysis to test whether board of directors elections and corporate governance affected earnings quality and the value relevance of earnin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
9
1
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 41 publications
(63 reference statements)
1
9
1
3
Order By: Relevance
“…A literatura apresenta evidências de que a qualidade do resultado pode depender de fatores como o nível de governança e o desempenho operacional (Chiang, Kleinman, & Lee, 2017), as expectativas de mercado (Cormier, Demaria, & Magnan, 2017), o nível de dívida (Bharath et al,2008), dentre outros. Em todas essas análises, na presença de gerenciamento de resultados via discricionariedade dos lucros, verifica-se um aumento dos custos para a empresa associados à diminuição da qualidade dos lucros e de sua capacidade em prever alterações futuras do fluxo de caixa (Dechow et al, 2010).…”
Section: Fundamentação Teóricaunclassified
“…A literatura apresenta evidências de que a qualidade do resultado pode depender de fatores como o nível de governança e o desempenho operacional (Chiang, Kleinman, & Lee, 2017), as expectativas de mercado (Cormier, Demaria, & Magnan, 2017), o nível de dívida (Bharath et al,2008), dentre outros. Em todas essas análises, na presença de gerenciamento de resultados via discricionariedade dos lucros, verifica-se um aumento dos custos para a empresa associados à diminuição da qualidade dos lucros e de sua capacidade em prever alterações futuras do fluxo de caixa (Dechow et al, 2010).…”
Section: Fundamentação Teóricaunclassified
“…Moreover, because we include interaction terms in our regression models throughout the paper, multicollinearity is a relevant concern. This concern is common in the value relevance literature (e.g., Chiang et al, 2017). Therefore, we check variance inflation factors (VIFs) for each of the variables included in all of our models to ensure that they are below the typically suggested cutoff of 10 (Cohen, Cohen, West, & Aiken, 2003, p. 423).…”
Section: The Impact Of Accounting Comparability On the Value Relevamentioning
confidence: 99%
“…We argue that, because accounting comparability increases both the quantity and quality of financial information available to investors, it improves the value relevance of the key financial metrics examined in previous literature-earnings and book value of equity (e.g., Bae & Jeong, 2007;Burgstahler & Dichev, 1997;Chiang, Kleinman, & Lee, 2017;Clarkson, Hanna, Richardson, & Thompson, 2011). Our examination focuses on accounting comparability for the following three reasons.…”
Section: Introductionmentioning
confidence: 99%
“…Chalevas and Tzovas [2] found that the mandatory corporate governance mechanisms decrease firms' weighted average cost of capital, increase firm's financing, and do not influence firms' effectiveness and earnings manipulation. Chiang et al [3] found that elections led to lower earnings quality, but better corporate governance led to greater earnings quality. In the presence of board of elections, earnings reduce value relevance, but book value increases value relevance.…”
Section: Introductionmentioning
confidence: 99%
“…One of the approaches in determining the value of intrinsic stocks is the price book value (PBV), which shows how far a company is capable in creating firm values that is relative to the total of invested capital. Higher PBV ratio implies that a company has created values for its shareholders [3][4][5].…”
Section: Introductionmentioning
confidence: 99%